The quality of informed consent obtained for orthopedic surgeries—elective versus trauma: A prospective interview-based study. (8th May 2019) - Shemesh, S; Sidon, E; Heller, S; Cohen, N; Kosashvili, Y; Dovrat, R; Velkes, S; Burg, A
Background: Orthopedic surgeons routinely obtain informed consent prior to surgery. Legally adequate informed consent necessitates a thorough discussion of treatment options and risks and proper documentation. However, the quality of informed consent in orthopedic trauma patients is an under-researched area. Purpose: To assess the quality of the informed consent process in trauma compared with elective orthopedic patients and to assess patients' emotional state at the time of signing consent form. Methods: Sixty-two consecutive patients undergoing either elective total joint arthroplasty ( N = 32) or orthopedic trauma surgery ( N = 30) were included. The data were collected through personal interviews using a proposed informed consent score. The interviews were held after obtaining the informed consent and before the index procedure. Patients were asked to describe their diagnosis, the surgical procedure, its' benefits, and risks as well as alternative treatments. Results: Mean age differed significantly between elective and trauma group patients (66.1 vs. 51.6, respectively, p < 0.01), while gender and education level were comparable ( p = 0.075, p = 0.55, respectively). The quality of consent was significantly better for patients with post-high-school education compared to elementary education level (consent score: 16.9 ± 4.1 vs. 12.2 ± 5.5, p = 0.021). Patients in the elective group showed an overall higher quality of consent, as reflected by a mean score of 17.03 ± 4.2 versus a mean score of only 13.73 ± 4.7 in the trauma group ( p = 0.005, 95% CI: 1.02–5.57). Specifically, trauma patients demonstrated a lower comprehension of the diagnosis, the benefits of surgical treatment, the possible complications, and the expected postoperative course. Conclusion: Patients undergoing trauma surgery are significantly more likely to have an inadequate understanding of the proposed treatment. These findings raise questions concerning the validity of consent from trauma patients.